A WXW Motif Is Required for the Anticancer Activity of the TAT-RasGAP(317–326) Peptide - Barras, David (American Society for Biochemistry and Molecular Biology, 2014)
TAT-RasGAP(317–326), a cell-permeable 10-amino acid-long peptide derived from the N2 fragment of p120 Ras GTPase-activating protein (RasGAP), sensitizes tumor cells to apoptosis induced by various anticancer therapies. This RasGAP-derived peptide, by targeting the deleted in liver cancer-1 (DLC1) tumor suppressor, also hampers cell migration and invasion by promoting cell adherence and by inhibiting cell movement. Here, we systematically investigated the role of each amino acid within the RasGAP(317–326) sequence for the anticancer activities of TAT-RasGAP(317–326). We report here that the first three amino acids of this sequence, tryptophan, methionine, and tryptophan (WMW), are necessary and sufficient to sensitize cancer cells to cisplatin-induced apoptosis and to reduce cell migration. The WMW motif was found to be critical for the binding of fragment N2 to DLC1. These results define the interaction mode between the active anticancer sequence of RasGAP and DLC1. This knowledge will facilitate the design of small molecules bearing the tumor-sensitizing and antimetastatic activities of TAT-RasGAP(317–326).